2014
DOI: 10.1002/app.40953
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polyetheretherketone particle suspensions for electrophoretic deposition

Abstract: Suspensions of polyetheretherketone (PEEK) using mixture of ethanol and isopropanol as solvent were prepared to carry out PEEK electrophoretic deposition (EPD). The rheological behavior and suspension structure of PEEK particles dispersed in co‐solvents were investigated over a range of pH values (1–10) and shear rates (γ = 101−3 × 102 s−1). These PEEK suspensions generally exhibited a pseudoplastic flow behavior, indicating the occurrence of particle aggregation in the liquid medium. The maximum solids fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…However, it has also been used for purification, particle size reduction (in sizes ranging from nano-to micrometres), and development of specific particle morphology [32,33] and sonochemical synthesis [34][35][36]. Despite its benefits, TS has been rarely used in preparing PEEK suspensions for EPD [37][38][39] in comparison with bath ultrasonication [6,[40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has also been used for purification, particle size reduction (in sizes ranging from nano-to micrometres), and development of specific particle morphology [32,33] and sonochemical synthesis [34][35][36]. Despite its benefits, TS has been rarely used in preparing PEEK suspensions for EPD [37][38][39] in comparison with bath ultrasonication [6,[40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…PEEK suspension has been extensively utilized in various investigations, including wet powder impregnation for the preparation of continuous fiber reinforced PEEK prepreg tape, biocompatible material synthesis containing PEEK, and coating on the fiber surface during composite production. [28][29][30][31] PEEK resin particles are insoluble and exhibit poor dispersion in water, however, they are relatively well dispersed in certain organic solvents. 32,33 Silvia et al 28 prepared a PEEK suspension using a mixture of ethanol and isopropanol as a solvent to enable the subsequent PEEK particles' electrophoretic deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Most resin powders have hydrophobicity and are difficult to disperse directly in water. Therefore, it is necessary to add a certain amount of surfactant to achieve uniform dispersion of the powder 24–26 . Surfactants can effectively reduce the interfacial tension between the particles and the solvent.…”
Section: Introductionmentioning
confidence: 99%
“…The suspension can remain stable for a certain period of time. 27 However, it was found that settlement stratification appeared soon after suspension was standing. In addition, the quantitative analysis of PEEK suspension stability and delamination time is lacking.…”
Section: Introductionmentioning
confidence: 99%